Economics: A Science of Meaning - Carmelo Ferlito (ZBW – Leibniz Information Centre for Economics, 2018)
In this paper I will define economics following a different general approach to economic problems, an approach that, because of its emphasis on meaning, has been called `radical subjectivism' (Storr, 2017). In the light of this approach, it is possible to develop a general theory for the economic system, with the possibility of globally responding to economic questions within a broad paradigm. Moreover, such a paradigm has to incorporate two fundamental elements disregarded by mainstream economics: real people and real time.
Keywords: A11; 330; Economics; Meaning; Real Time